The Influence of Parenting Style on Juvenile Delinquency in Barangay Bitungol Norhomes Norzagaray Bulacan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Delinquency and parenting are frequently linked to the effects of additional factors, such asthe subject’s gender, color, or ethnicity adolescent. Effects of family structure on crime.Among the family types examined were single mothers, fathers who are single, stepmothersand stepfathers, and intact families. This study demonstrates a strong impact of genderinteraction. Thus, the phrase “juvenile delinquency” refers to a wide category that connectsteenagers in two important aspects. Firstly, they will always be between the ages of 18 and 24.Secondly, the fact that they were charged with a crime and appeared in court. Numerousthings can lead to juvenile delinquency. Peer pressure, being close to violence, intelligence,being around others who are criminals, and specific hereditary features are all factors.This chapter presents the statistical data related to the profile and perception of therespondent and the listed problem. This part of the study discusses the correspondinganalysis, presentation, and interpretation of the data result. Researchers explain the overallresult gathered from the perspective of parents. The majority of the data is agreed upon by therespondents, and the presents present their perceptions to the researcher.The quality of parental relationships with the juvenile is important in reducing juveniledelinquency trends. Parents’ role model is paramount to juveniles. Punishment by spankingdoes not necessarily instill discipline in children. On the contrary, this is a contributing factor todelinquency as juveniles translate this to hatred. Most parents do not monitor their juvenilebehavior appropriately. As a result, they were unable to identify and curb behavior beforegetting out of hand. Some juveniles came from a family with both parents but still ended up asjuveniles. This means it’s not the mere presence of parents but the quality of interpersonalrelationships experienced. In addition, the family rules and regulations need to be developedby both the parents and children.
Keywords: Womens & Childrens Health